Survey on electronic procurement implementation in Malaysia construction companies - Ng, Kim Aik (2005)
Construction material procurement is one of the most important sections in the construction project life cycle. The procurement concept is moving ahead from traditional manual paper-based to electronically-based due to improvement in Internet and World Wide Web technology. In such a highly competitive environment nowadays, it is necessary for every construction company to maintain an efficient and effective material procurement to cut administration cost and to keep abreast of the market condition to procure materials at the right price, quality and time. Suggested by its name, electronic procurement (E-procurement) is the application of Internet technology in material procurement. The main objective of this study is to identify factors affecting implementation of E-procurement and Malaysia construction companies practice and strategy towards it. Research methodology includes comprehensive literature review and questionnaire survey. Through literature review, questionnaire was designed and distributed to the targeted survey respondent situated in Kuala Lumpur and Selangor using postal mail format. From the survey responded, the factors and strategy were analyzed and identified. As a conclusion, the main objective of this project has been achieved. The results obtained from the survey shown that perceived value, trust on Information Technology and trust on supplier are the important determinant factors towards implementation of Eprocurement. Also, it has been identified that construction companies are aware of the development of E-procurement but they will not commit major resources towards implementing it